Comparative Study of Local and Imported Enzymes in Improving the Nutritional Values of Agricultural Waste on Performance and Economic Efficiency of Iraqi Lambs - Mustafa AL-Khateeb; Adel ALhmdani; Sundus mohammed (مجلة الانبار للعلوم البيطرية)
In the current study, we use 25 local Iraqi lambs. With initial body weight (24) kg. The lambs were randomly divided into five treated groups, the first group without treatment as control, the second and third treated with 20%and 40% Agricultural Waste treated with trade enzymes, fourth and fifth treatment 20%and 40% Agricultural Waste treated with local enzymes. The result demonstrated a significant (P<0.01) increase in the quantity of roughages, total feed intake, Neutral Detergent Fiber (NDF) and Acid Detergent Fiber( ADF) and Lignin (ADL) in T5 followed by T4 compared with others treated groups and showed a significant (P<0.01) increase in the digestibility of NDF ,ADF in T4, T5 compare with other treated groups. While T5and T4 recorded Superiority increase in weight gain, and significant improvement in economic cost efficiency with ratio improvement of 5.90, 5.97 % respectively